PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN IZIN VISA KUNJUNGAN DI WILAYAH KERJA KANTOR IMIGRASI KELAS II TANJUNG BALAI KARIMUN - Sapriyanto (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
Abstract : The purpose of this study was to determine the law enforcement system for misuse of the visit visa permit in the working area of ​​Tanjung Balai Karimun Class II Immigration Office. This study used qualitative research methods. The research results show, there are several problems that occur including, namely; overstaying, abuse of residence permit, incomplete documents and entry not passed (Immigration Check Points). Tanjung Balai Karimun Class II Immigration records for 2019 until 2020 show cases of legal violations that often occur in the Tanjung Balai Karimun Class II Immigration Office area, namely overstaying, which exceeds the time limit given by Tanjung Balai Karimun Immigration officials. The number of cases that occurred from the beginning of 2019 to April 2020 was 7 cases. Based on the existing problems, the perpetrators of criminal acts were sentenced to deportation from the Tanjung Balai Karimun area. The Tanjung Balai Karimun Class II Immigration Office in terms of supervision in the field cooperates with related agencies, namely; Port Office and Port Authority, Port Health Office, Customs and Excise, National Police, Indonesian Armed Forces, Ministry of Religion, Transportation Office, and assisted by all levels of the community in Tanjung Balai Karimun